APPLICATION OF NATURAL ZEOLITE AS A COMPONENT OF CATALIST BUFFER FOR HYDROGENATION REACTION OF CO2 AND CRACKING OF PALM OIL - Setiadi Setiadi; Yanes Darmawan; R. Melisa Fitria (Jurnal Zeolit Indonesia, 2007)
This research was started with making a catalyst of CuO/ZnO/ZSM-5 with copresipitation method which using nitrate salts of Cu and Zn at buffer of zeolite ZSM-5 with loading (weight CuO and ZnO into their buffer) 10%, 20%, 30%, 40% and the pure of ZSM-5. The product of catalyst is then activated tested by hydrogenation reaction, where CO2 gas become the methanol by reacting of CO2 dan H2 into unggun reaction in operation condition: the pressure of 25 bar, with temperature at 250ºC, feeding ratio CO2/H2 = 1 : 3. The making catalyst of CuO/ZnO/ natural zeolite each with impregnation method and physical mixing at the best loading in the result of activities test from all of catalyst CuO/ZnO/ZSM-5 by the results of preparation of copresipitation methods. The result of catalyst test indicate that the methanol (CH3OH) can be made of the main feeding of CO2 and H2 gas with catalyst of CuO/ZnO/ZSM-5 and catalyst of CuO/ZnO/ natural zeolite from the result of copresipitate preparation, impregnation and physical mixing. The test of CuO/ZnO/ZSM-5 catalyst resulting of preparation copresipitation indicate that catalyst with loading 30% yielding methanol (0.1359%). The method of copresipitation is the best among the other methods. We also obtained the buffer of natural zeolite from Malang can also give yield of methanol product although it's not as high as with buffer of ZSM-5. The cracking reaction of oil palm using a natural zeolite toproduce gasoline fraction of hydrocarbon compound in fixed bed reactor in atmospheric pressure and the temperature at 350-500ºC. The natural zeolite with addition of B2O3 0-20% is used as catalyst with variabel temperature, type of feeding and B2O3 addition. The characteristic for seeing the surface area with BET method and crystalization of B2O3 with XRD method. Addition of B2O3 optimum of 5% gave the yield 52.3% for feeding POME and 38% oil palm and methanol.